Optimization conversion of willow biomass derived from phytoremediation into value-added hydrochars: Effects of temperature and medium on Cd/Zn distribution and application potentials - Zhao Bo; Li Haihua; Yang Xiaoli; Zhao Weibin; Chen Yan; Di Dongliu; Xiao Jiang; Chen Guangcai (Energy Conversion and Management: X)
Effective treatment of plant biomass with potentially toxic elements (PTEs) is crucial for phytoremediation. Hydrothermal carbonization (HTC) offers an economical and eco-friendly solution by converting biomass into high-value hydrochar. However, the effects of reaction temperature and medium on the characteristics and metals distribution in hydrochars from PTEs-containing biomass remain unclear. This study explores the effects of different hydrothermal temperature (180–240 °C) and reaction media (H2O, HCl, H2SO4, H3PO4) on the hydrothermal properties of willow biomass containing PTEs, and the distribution and transfer rules of PTEs (Cd and Zn) and the application potential of hydrochar. The results indicated that hydrothermal temperature and acid medium significantly influenced WB conversion, affecting hydrochar properties such as carbonization degree and surface functional groups. Higher hydrothermal temperatures enhanced Cd and Zn fixation in the solid phase, while acid facilitated their migration to the liquid phase. More than 91.08 % of Cd and 88.41 % of Zn in the acid-added system are migrated into the liquid phase at hydrothermal temperature of 180 °C Hydrochar prepared under 180 °C and H3PO4 exhibited excellent adsorption performance for Cd2+ and Cu2+ (2.17 mg/g and 34.38 mg/g, respectively) in aqueous solution. Additionally, hydrochars exhibit high calorific values (20.52–28.01 MJ/kg), suggesting their potential as biofuel. This study provides technical foundation to support the resource processing and safe utilization of forest biomass containing PTEs.